A psychological perspective on students’ attitudes toward mathematics and self-confidence in contextual role-playing learning - Getut Pramesti; Sulasih Sulasih; Eko Santoso; Retno Dwi Astuti; Adhitya Try Mahardika; Samuel Ardika Santosa; Salsabila Mutmainah; Pinasthi Soesilo Oetomo; Evellyn Sandra Auliya; Yusril Gibran Tsaqih; Winandita Amelia Douryat (Personifikasi: Jurnal Ilmu Psikologi, 2026)
The research examined the implementation of contextual role-play learning and its relationship with students’ attitudes toward mathematics and self-confidence from a psychological perspective. A quantitative approach was employed using descriptive and inferential analyses. The population comprised Grade VII students enrolled at a public junior secondary school in rural Karanganyar, Surakarta, during the 2025/2026 academic year. Data were collected from March to May 2026. The sample consisted of 290 students aged 12–13 years, including 111 students who participated in contextual role-play learning and 179 students who participated in non-role-play learning. Participants were selected using cluster random sampling. Significant between-group differences were found in students’ attitudes toward mathematics (p = .004), particularly perceived anxiety (p .001). The engaging, enjoyable, and cooperative environment created through role-play activities helped students participate more comfortably in mathematics lessons. Contextual role-play learning was also associated with higher mathematics self-confidence (p .001), particularly in the self-confidence (p .001) and success-orientation (p .001) dimensions. Psychologically, contextual role-play learning supported confidence by reducing perceived anxiety and making mathematics more meaningful, interactive, and connected to real-life experiences. The findings suggest that contextual role-play activities can create a supportive learning environment that strengthens students’ confidence in achieving success in mathematics.